Inequality Within and Among Nations - Lovell, Michael C. (Journal of Income Distribution®, 1999)
This paper looks at both within and among country inequality utilizing data for the 82 countries for which comparable data are available from the 1996 World Development Report. In the spirit of Dalton (1920) and Atkinson (1970), this paper reports estimates for the welfare loss arising from inequality. The paper also explores the implications of Duesenberry style interdependent utility functions and evaluates the appropriateness of the Gini coefficient as a possible measure of "relative deprivation". In 18% of the pairwise comparisons of inequality in different countries, the situation is ambigious in the sense that neither country Lorenz dominates the other (Shorrocks, 1982). Generalized Lorenz curves leave ambigious 16% of paired welfare comparisons. The data generated a surprisingly stable empirical result: for any utility functrion satisfying Dalton's Principle of Proportionality of Transfers, the loss of welfare rising from within country inequality is approximately 40% of the loss caused by inequality among nations.